EEG topographical maps analysis for 2D and 3D video game play - Khairuddin, R.N.H.R. (IEEE Computer Society, 2014)
Despite the growth of 3D applications, the effects of 3D technology on humans are relatively unknown and are still inconclusive. As we aimed to investigate the general effect of 3D game, we analyzed the dynamical changes in human brain using the EEG power absolute and coherence measures from brain topomaps. Our findings showed an increase in theta and alpha bands at the frontal and occipital regions for 3D game play, while in 2D, higher beta and gamma activity was observed especially in temporal lobes. We also found similar results for 3D Active versus 3D Passive where 3D Passive theta and alpha power was relatively higher. Based on these results, we could deduce that 3D game play required more data processing which involved working memory as well as attention. Even with differences in activation, the overall user preference was equally divided for 3D Active and 3D Passive. Â© 2014 IEEE.